Language Skills in Business Context: A Bibliometric Analysis Using the VOS Viewer Application - Suprayogi, Yogi; Luckyardi, Senny; Kurnia, Dede; Khairusy, Mirza Abdi (Journal of Language Learning and Assessment, 2024)
Purpose The purpose of this study is to use VOSviewer to conduct a bibliometric examination of language skills in a business context. A quantitative description method is employed in this investigation. Methodology The data utilized in this study came from Google Scholar search results for the term "Language skills in business context," which were obtained utilizing the publish or perish program. The data source was taken from the Google Scholar database for the period 2013 – 2023. The total documents found during the last 10 years were 616 documents. Results/Findings Based on the research results, it was found that the number of publications regarding the test language skills in business contex experienced fluctuations. The results of mapping the article data produce three forms of visualization, namely network visualization, overlay, and density. Implications The study provides valuable insights into the evolution, methodologies, and trends within research on language skills in a business context, emphasizing the importance of bibliometric analysis in understanding scholarly landscapes.